Human Resource Procurement Strategy in Empowering Local Labor in Luwu District (Case Study of PT. Bumi Mineral Sulawesi) - Palanggi, Andi; Jusriadi, Edi; Anggoro, Yusuf Alfian Rendra (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the strategy of human resource procurement through forecasting needs and recruitment and selection carried out by PT. Bumi Mineral Sulawesi. This type of research is descriptive with a qualitative approach using case studies. The informants in this study amounted to 8 people. The data collection techniques used were Observation, interviews, documentary techniques and field note techniques. Data analysis in this study was Data condensing, data display and drawing conclusions. The results of the study showed that in the process of forecasting workforce needs at PT. BMS uses two methods, namely: the Delphi technique for forecasting production activities, where the company in this case uses mining production experts from China in compiling the Man Power Planning production. In the recruitment and selection process, the company also uses two methods, namely: open recruitment for skilled workers, where job posting is done online. In the company there are several rules or policies that apply in efforts to empower local workers. In terms of workforce placement, it is carried out with the principles of humanity, justice, objectivity, efficiency and effectiveness, which are carried out in accordance with job postings after going through selection.